2023
DOI: 10.1001/jamanetworkopen.2023.12022
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning–Based Prognostic Model for Patients After Lung Transplantation

Abstract: ImportanceAlthough numerous prognostic factors have been found for patients after lung transplantation (LTx) over the years, an accurate prognostic tool for LTx recipients remains unavailable.ObjectiveTo develop and validate a prognostic model for predicting overall survival in patients after LTx using random survival forests (RSF), a machine learning algorithm.Design, Setting, and ParticipantsThis retrospective prognostic study included patients who underwent LTx between January 2017 and December 2020. The LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Gao et al reported that the incidence of PMV (defined as > 72 h) was 31.9%, excluding ECMO-supportive patients 10 . Since PMV is not clearly defined in the literature, the PMV in this study was defined according to the previous large-scale retrospective study, where the mean ventilation time of LTx patients was 5 days 11 . Therefore, PMV was defined as > 5 days in the current research.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al reported that the incidence of PMV (defined as > 72 h) was 31.9%, excluding ECMO-supportive patients 10 . Since PMV is not clearly defined in the literature, the PMV in this study was defined according to the previous large-scale retrospective study, where the mean ventilation time of LTx patients was 5 days 11 . Therefore, PMV was defined as > 5 days in the current research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Tian et al explored the development and evaluation of a ML-based prognostic model to predict survival outcomes for patients following lung transplantation ( 41 ). Utilizing data from the United Network for Organ Sharing (UNOS), the authors developed a Random Survival Forest (RSF) model, incorporating a comprehensive set of clinical variables.…”
Section: Prognosticationmentioning
confidence: 99%